Market Power and Inefficiency: A Contracts Perspective. - Vickers, J (1996)
This paper surveys the economics of market power from the perspective of contract theory. Various practices that might be of competition policy concern including price discrimination, quantity discounts, bundling, vertical integration, and contracts with customers -- are discussed in terms of constraints on profit maximization, chiefly arising from incomplete information and credible commitment problems. First, the exploitation of pure monopoly power over final consumers or downstream, firms is discussed. Then motives for anticompetitive behavior towards rival firms are considered, including avoidance of profit dissipation, extraction of rival surplus, and exploitation of customer disunity.